The utility of urinary CD80 as a diagnostic marker in patients with renal diseases. Issue 1 (December 2018) - Minamikawa, Shogo; Nozu, Kandai; Maeta, Shingo; Yamamura, Tomohiko; Nakanishi, Keita; Fujimura, Junya; Horinouchi, Tomoko; Nagano, China; Sakakibara, Nana; Nagase, Hiroaki; Shima, Hideaki; Noda, Kenta; et al.
Abstract CD80, which regulates T cell activation, may provide a differential diagnostic marker between minimal change disease (MCD) and other renal diseases, including focal segmental glomerular sclerosis (FSGS). However, recent reports show contrasting results. Therefore, we evaluated the utility of urinary CD80 as a diagnostic biomarker. We collected 65 urine samples from 55 patients with MCD (n = 31), FSGS (n = 4), inherited nephrotic syndrome (n = 4), Alport syndrome (n = 5) and other glomerular diseases (n = 11), and control samples (n = 30). We measured urinary CD80 levels by ELISA. Urinary CD80 (ng/gCr) (median, interquartile range) levels were significantly higher in patients with MCD in relapse (91.5, 31.1–356.0), FSGS (376.2, 62.7–1916.0), and inherited nephrotic syndrome (220.1, 62.9–865.3), than in patients with MCD in remission (29.5, 21.7–52.8) (p < 0.05). Elevation of urinary CD80 was observed, even in patients with inherited nephrotic syndrome unrelated to T cell activation. Additionally, urinary CD80 was positively correlated with urinary protein levels. Our results suggest that urinary CD80 is unreliable as a differential diagnostic marker between MCD in relapse and FSGS or inherited kidney diseases. Increased urinary CD80 excretion was present in all patients with active kidney disease.